The Concept of Criminal Liability of State-Owned Enterprises in The National Criminal Code and State-Owned Enterprises Law - Amri, Ulil; Syafruddin, Andi Ummu Fauziyyah; Tombi, Johan Tri Noval Herdian; Luthfan, Gusti Fadhil Fithrian (Universitas Islam Negeri Alauddin Makassar, 2025)
Following the enactment of the latest State-Owned Enterprises Law, various state-owned enterprises remain as accountable corporate entities, particularly with the implementation of the National Criminal Code, which requires harmonization from both a normative perspective and in terms of accountability. This study aims to analyse the criminal liability of SOEs under the National Criminal Code and the harmonisation of this concept with Law No. 1 of 2025. The research employs a normative approach using both a conceptual and a legislative method. The legal materials are sourced from primary and secondary legal materials, analyzed using qualitative prescriptive analysis. The results show that 1) State-owned enterprises can be held criminally liable under Article 45 of the National Criminal Code, which categorizes state-owned enterprises as entities that can be held criminally liable. The determination of liability must be based on the degree of corporate fault under the National Criminal Code, as seen from the aspect of internal prevention, 2) SOEs, as entities that control the livelihoods of many people, should also consider restorative aspects, where the purpose of sanctions is not only to provide a deterrent effect, but also to encourage structural improvements by taking into account the principles of effectiveness and efficiency.